Clinicians' attitudes regarding withdrawal of left ventricular assist devices in patients approaching the end of life1. (November 2013) - Swetz, Keith M.; Cook, Katlyn E.; Ottenberg, Abigale L.; Chang, Nou; Mueller, Paul S.
<x xml:space="preserve">Abstract</x> Aims Left ventricular assist devices (LVADs) are implanted to support the circulation of patients with advanced heart failure. Patients approaching death, or their surrogates, may request withdrawal of LVAD support. We sought to study the attitudes and practices of heart failure clinicians regarding withdrawal of LVAD support in patients approaching death. Methods and results Using internet‐based and secure methods, we surveyed members of the European Society of Cardiology‐Heart Failure Association (ESC‐HFA), the International Society for Heart and Lung Transplantation (ISHLT), and the Heart Failure Society of America (HFSA) to assess their attitudes and practices regarding LVAD withdrawal for patients approaching death. The results indicated that clinicians have varied attitudes and practices regarding withdrawing LVAD support in these patients. Furthermore, ESC‐HFA clinicians (primarily European) and ISHLT and HFSA clinicians (primarily North American) differed in their attitudes and practices regarding withdrawal of LVAD support, particularly its ethical and legal permissibility. For example, more European clinicians than North American clinicians regarded withdrawing LVAD support as a form of euthanasia. Conclusion Opinions and level of comfort with LVAD withdrawal vary among clinicians. Clinicians should be aware of suggested approaches or guidelines for managing requests for withdrawal of LVAD therapy.